(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This paper examines the major territorial varieties of English pronunciation across different regions of the world, focusing on phonological systems, accent features, and vowel and consonant variations. It provides a comparative analysis of British Received Pronunciation, General American, Australian, Canadian, Irish, Scottish, South African, and various emerging World Englishes.